2019
DOI: 10.1002/advs.201901613
|View full text |Cite
|
Sign up to set email alerts
|

Donor Derivative Incorporation: An Effective Strategy toward High Performance All‐Small‐Molecule Ternary Organic Solar Cells

Abstract: small-molecule acceptor are currently attracting enormous attentions due to their distinct advantages such as monodispersion, easy purification, and scalability with negligible batch-to-batch variation. [1][2][3][4][5] Tremendous progress has been made in the past years on rational molecule design, device engineering, and interface modification, leading to over 10% power conversion efficiencies (PCEs) in ASM OSCs with fullerene derivatives as the electron acceptor. [6][7][8][9] However, the difficulties of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
76
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 51 publications
2
76
0
Order By: Relevance
“…Similarly, the IDIC‐4F‐based BHJ film displays Rq of 1.88 nm, which is obviously larger than that of the IDIC‐based counterpart (1.43 nm). As the AFM phase images indicate, relative to the IDIC‐based BHJ film, the IDIC‐4F‐based blend film presents a uniform yet more obvious nanofibrillar network (Figure b,d), which is advantageous for both interface contact and charge transport (Table ). As shown in the TEM images, the IDIC‐4F BHJ film displays clear phase separation with a scale of ≈25 nm and a clear donor/acceptor interpenetrating network, which facilitates exciton dissociation and charge transport.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the IDIC‐4F‐based BHJ film displays Rq of 1.88 nm, which is obviously larger than that of the IDIC‐based counterpart (1.43 nm). As the AFM phase images indicate, relative to the IDIC‐based BHJ film, the IDIC‐4F‐based blend film presents a uniform yet more obvious nanofibrillar network (Figure b,d), which is advantageous for both interface contact and charge transport (Table ). As shown in the TEM images, the IDIC‐4F BHJ film displays clear phase separation with a scale of ≈25 nm and a clear donor/acceptor interpenetrating network, which facilitates exciton dissociation and charge transport.…”
Section: Resultsmentioning
confidence: 99%
“…Traditional ASM OSCs consist of a small‐molecule electron donor (typically based on donor moieties using benzodithiophene [BDT], thiophene, dithienosilole [DTS], and indacenodithiophene [IDT], etc. ) and fullerene derivatives as electron acceptors (e.g., PC 61 BM and PC 71 BM), which have resulted in an over 11% power conversion efficiency (PCE) due to the concerted efforts in rational molecular design and device engineering . However, fullerene acceptors suffer from several drawbacks, such as their weak absorption in the visible and near‐infrared (NIR) range, limited tunability of energy levels, and poor thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…The E loss values for OSCs based on SVA‐treated SM1:MPU4 and SM1:MPU1 are 0.42 and 0.53 eV, respectively. These values are amongst the lowest for any small‐molecule OSC, since the E loss in the BHJ‐based OSCs can be reduced by decreasing the energy offsets in the either HOMO or the LUMO offsets between the electron donor and acceptor units used in the BHJ active layer . The LUMO energy levels of MPU4 and MPU1 are similar (Table ).…”
Section: Resultsmentioning
confidence: 92%
“…In the past, most of ternary OSCs were based on conjugated polymers as donor but there are limited reports on all‐small‐molecule ternary OSCs. Recently, Tang et al have reported all‐small‐molecule ternary OSCs based on a small‐molecule donor and PC 71 BM and NFA, and achieved an overall PCE of 10.14% . The weight ratio between MPU4 and PC 71 BM was altered while keeping the weight ratio of SM1 constant.…”
Section: Resultsmentioning
confidence: 99%
“…Of all the third generation solar cell technologies (i.e., organic solar cells, perovskite solar cells, and dye-sensitized solar cells, and so on), bulk-heterojunction (BHJ) polymer solar cells (PSCs) have attracted broad academic and industrial interests, because of attractive features including flexibility, lightweight, large area, low-cost production, and environmental friendliness [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. The photovoltaic performance of BHJ PSCs was highly dependent on the semiconductor materials used as the photoactive layer.…”
Section: Introductionmentioning
confidence: 99%